Description of Operations - The New Cement Plant of the Universal Atlas Cement Company at Northampton, Pennsylvania (Mining Tech., Sept. 1943, T.P. 1619) - L. G. Sprague (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1948)
The fact that this latest and most modern of the Universal Atlas Cement Company's plants at Northampton, Pa., is the fifth to be built on these same properties, and their development has been coincidental with the development of the portland cement industry in the United States, makes it appropriate to sketch briefly the history of the successive steps. In 1889 the original Atlas Portland Cement Co. started its first plant at Coplay, Pa., which is just across the Lehigh River from the present operation. Here the first successful rotary kiln was operated. These kilns were 6 ft. in diameter and 60 ft. long; they used oil for fuel until 1895, when the company developed the first burner for pulverized coal. Shortly thereafter the Atlas company acquired property on the Northampton side of the river and built its plants Nos. 2, 3 and 4 within the following 10 years. During the same period the production of portland cement in the country was increasing rapidly; owing largely to the development of the rotary kiln and improved grinding machinery, which lowered the cost and improved the quality of cement. The general tendency has been to increase the length of the kiln and grind both raw material and finished product Liner. In 1930 the Atlas Portland Cement Co. and the Universal Portland Cement Co. united to form the Universal Atlas Cement Co., and the same policy of improving the product has been continued. Because of the large amount of research carried on by manufacturers and consumers, including government agencies, there is a demand for cement of different chemical and physical characteristics for different kinds of structures. Hence many engineers in recent years have been asking for cements of certain definite chemical analyses, which they think are best for their particular jobs. This has compelled the manufacturer to make several different types of cement by variations of chemical composition. These are generally made by adding silica, iron and lime to the standard mixture, which necessarily increases the cost of the product. Therefore the Universal Atlas Cement Co., in planning the modernization of its Northampton plant, gave this particular phase of the problem considerable study. Research and experimentation have developed the practicability of making a wide variety of differently proportioned raw materials for cement by a process of subtraction rather than by addition. With such process, it is possible to discard the undesirable aluminates and silicates from the ample supply of impure limestone available from the company's property rather than by adding high-grade limestone obtained from distant sources. This procedure requires mineral separation by centrifugal sedimentation and froth flotation. Since the chemical and mineral constituents of Lehigh Valley "cement rock," together with the methods of separating them, have been thoroughly described in published